2009
DOI: 10.1159/000227772
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Gβγ Signaling Depends on Gα Subunit Coupling with G-Protein-Sensitive K<sup>+</sup> Channels

Abstract: Many neurotransmitters activate G-protein-gated inwardly rectifying K+ (Kir3) channels by stimulating G-protein-coupled receptors. However, in native systems, only receptors coupled to pertussis-toxin (PTX)-sensitive G proteins (Gi/Go) have been shown to be able to activate Kir3 channels through the βγ subunits of G proteins (Gβγ), whereas activation of receptors coupled to PTX-insensitive G proteins such as Gq or Gs do not activate Kir3 channels. The question remains as to how signaling specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…A second study showed that different combinations of recombinant and purified Gβγ dimers directly activated GIRK channels6. Today, there is agreement that Gβγ subunits activate GIRK channels and, although there have been no further experiments demonstrating that Gα activates GIRK channels, Gαi/o G proteins are still considered important regulators of GIRK channels affecting receptor specificity and basal channel activity82,84,85,92,99,100,169.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A second study showed that different combinations of recombinant and purified Gβγ dimers directly activated GIRK channels6. Today, there is agreement that Gβγ subunits activate GIRK channels and, although there have been no further experiments demonstrating that Gα activates GIRK channels, Gαi/o G proteins are still considered important regulators of GIRK channels affecting receptor specificity and basal channel activity82,84,85,92,99,100,169.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PTX-sensitive Gα subunits can associate directly with GIRK channels and alter channel gating84,85,98,99. In fact, Gα may also be involved in establishing receptor specificity such that stimulation of GPCRs that couple to only PTX-sensitive G proteins activate GIRK channels84,100. Third, spectroscopic studies with fluorescently tagged GPCRs, G proteins and regulator of G protein signaling (RGS) proteins, have provided details on the spatial relationship between proteins within this macromolecular signaling complex26,92,94,96,101,102 (see Box 2).…”
Section: A Macromolecular Signaling Complex For Girk Channelsmentioning
confidence: 99%
“…Many of the G proteincoupled receptor-dependent physiological processes inhibited by PTX are mediated by Gβγ subunits released from Gi/o proteins [28]. We found that inhibition of Gβγ with Gallein blocked CB2R activation-induced β-endorphin release.…”
Section: Discussionmentioning
confidence: 63%
“…G-protein βγ subunits activate GIRK channels through direct binding with amino- and carboxyl-ends of the channels [ 2 , 22 ]. The G-protein α subunit was not thought to be responsible for GIRK channel activation, but rather to be a regulator of the specificity of channel activation [ 4 , 23 ]. Among addictive substances, alcohol activates GIRK channels in a G-protein-independent manner [ 24 ], whereas cocaine and phencyclidine directly inhibit GIRK channels at toxic concentrations [ 25 , 26 ].…”
Section: Fundamental Function Of Girk Channels and Response To Addict...mentioning
confidence: 99%